2015
DOI: 10.3389/fpls.2015.00818
|View full text |Cite
|
Sign up to set email alerts
|

CrBPF1 overexpression alters transcript levels of terpenoid indole alkaloid biosynthetic and regulatory genes

Abstract: Terpenoid indole alkaloid (TIA) biosynthesis in Catharanthus roseus is a complex and highly regulated process. Understanding the biochemistry and regulation of the TIA pathway is of particular interest as it may allow the engineering of plants to accumulate higher levels of pharmaceutically important alkaloids. Toward this end, we generated a transgenic C. roseus hairy root line that overexpresses the CrBPF1 transcriptional activator under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Ultimately, coordinate regulation of the complete set of MIA biosynthesis genes will require a more complex combination of transcriptional activators and repressors. Indeed, several other TFs have been reported as positive or negative regulators of MIA genes, including G-box-binding factors (GBFs), the MYB TF box P-binding factor-1 (BPF1), WRKY1, AT-hook TFs and EAR-domain containing zinc finger TFs Sib eril et al, 2001;Pauw et al, 2004;Vom Endt et al, 2007;Suttipanta et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, coordinate regulation of the complete set of MIA biosynthesis genes will require a more complex combination of transcriptional activators and repressors. Indeed, several other TFs have been reported as positive or negative regulators of MIA genes, including G-box-binding factors (GBFs), the MYB TF box P-binding factor-1 (BPF1), WRKY1, AT-hook TFs and EAR-domain containing zinc finger TFs Sib eril et al, 2001;Pauw et al, 2004;Vom Endt et al, 2007;Suttipanta et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As for regulatory genes, overexpressing CrBPF1 increased the transcripts of ORCA3 , CrMYC1 , CrMYC2 , BIS1 , GBF2 and ZCTs , but little affected the expressions of ORCA2 and CrWRKY1 . Although overexpression of CrBPF1 could not obviously increase the accumulation of TIAs and even caused the decrease of serpentine, it could extensively regulate TIA pathway genes and increase the expression of TIA transcriptional repressors, which may be a good direction to the research of TIA biosynthesis [ 44 ].…”
Section: Transcriptional Regulation Of Tia Biosynthesismentioning
confidence: 99%
“…Many previous C. roseus engineering studies showed that the modification of TIA genes usually led to complex transcriptional changes in other pathway genes and transcription factors [16,17,33]. Similarly, the complicated mRNA changes in the TIA pathway regulators were triggered after inducing two vindoline pathway genes T16H and 16OMT.…”
Section: Discussionmentioning
confidence: 99%
“…and Str genes were enhanced after induction by JA and fungal elicitation, which suggests that CrMYC1 activates the expression of the Str gene [32]. CrMYC2 is postulated to act upstream of ORCA2 and ORCA3, activating their transcription [33].…”
Section: Regulation Of the Tia Pathwaymentioning
confidence: 99%
See 1 more Smart Citation